Praktik Poligami di Kalangan Pegawai Negeri Sipil Wanita yang Menjadi Istri Kedua - Ricca Anindya Putri (LPPM Universitas Ekasakti Padang, 2023)
Female civil servants are not allowed to become the second, third or fourth wife in Article 4 paragraph (2) of Government Regulation Number 45 of 1990, but before the existence of Government Regulation Number 45 of 1990, female civil servants could become the second, third or fourth wife of a man who was not a civil servant. Initially, the regulation of PP No. 10 of 1983 was amended by PP No. 45 of 1990 to include a prohibition on female civil servants becoming the second, third or fourth wife of either male civil servants or non-civil servants. There are several decisions in the Religious Courts, where judges decide on requests for polygamy permits that do not comply with the regulations regarding polygamy. Some of these decisions include Decision Number 0085/Pdt.G/2019/PA.Sel, 0306/Pdt.G/2017/PA.Gtlo and 0102/Pdt.G/2016/PA.Dgl. In the decision on the polygamy permit application, there was a discrepancy between the provisions of Article 4 paragraph (2) of Government Regulation Number 45 of 1990 and the three judge's decisions above. The existence of a polygamy permit granted which is not based on the provisions contained in Article 4 paragraph (2) of PP Number 45 of 1990, namely the second wife candidate of the applicant who applies for a polygamy permit has a status as a Civil Servant. The result of this study is the judge's consideration in granting the applicant's request for permission to polygamy with a woman who is a civil servant is by submitting a statement letter ready to bear the risks caused by his marriage to the applicant. The judge overruled Article 4 Paragraph 2 of Government Regulation Number 45 of 1990 on the condition that the parties make a statement to bear the risk. The risk in question is dishonorable dismissal as a civil servant and the marriage can be annulled by the relevant agency or official. The parties must know and understand the risks they will face in applying for a polygamy license where the second wife is a woman who is a civil servant.